Yearbook of Muslims in Europe. - Nielsen, Jørgen S. (Yearbook of Muslims in Europe, 2012)
The Yearbook of Muslims in Europe provides an up-to-date account of the situation of Muslims in Europe. Covering 46 countries of Europe in its broader sense, the Yearbook presents a country-by-country summary of essential data with basic statistics and evaluations of their reliability, surveys of legal status and arrangements, organisations, et cetera Data have been brought up to date from the previous volume. From 2012 onwards, the Yearbook of Muslims in Europe will continue as two separate publications. The Yearbook will remain the annual reference work for country surveys on Muslims in Europe. The former article and review sections of the Yearbook are now published as the new Journal of Muslims in Europe . The Yearbook of Muslims in Europe remains an important source of reference for government and NGO officials, journalists, and policy makers as well as scholars.